Tick tock [large type] - Patterson, James, 1947- (Patterson, James, 1947- Detective Michael Bennett thriller., 2011)
NYC's number one detective, Michael Bennett, has a huge problem-- someone is recreating the crimes of infamous killers from New York's history. Bennett enlists the help of a former colleague, FBI Agent Emily Parker.